Formulasi Pupuk Organik Pelet Cangkang Telur Ayam dan NPK sebagai Media Pertumbuhan Tanaman Tomat (Solanum lycopersicum): Formulation of Chicken Egg Shell Organic Pellet Fertilizer and NPK as Growth Media for Tomato Plants (Solanum lycopersicum) - Susilo, Achmadi; Paga, Maria Ignatia (Agrotechnology Study Program, Faculty of Agriculture, Wijaya Kusuma Surabaya University, 2023)
This study aimed to determine the effect of chicken eggshell organic fertilizer pellets (POPe) and NPK on the growth and yield of tomato plants. The research was conducted at the Experimental Garden of the Faculty of Agriculture, Wijaya Kusuma University Surabaya from April to August 2022. The experiment used a Randomized Block Design (RBD) factorial with two factors, namely: Factor (1) POPe chicken eggshell (P) and Factor (2) NPK dose (K). Each treatment was repeated three times with P0 (without POPe treatment), POPe chicken eggshell treatments consisted of P1 (7.5 gr POPe), P2 (15 gr POPe), P3 (22.5 gr POPe) and K0 (without NPK dose), NPK fertilizer doses of K1 (9 gr NPK). The results showed that the use of POPe and NPK on tomato plants had no effect on their growth and yield.